2019
DOI: 10.1093/scan/nsz048
|View full text |Cite
|
Sign up to set email alerts
|

Asking ‘why?’ enhances theory of mind when evaluating harm but not purity violations

Abstract: Recent work in psychology and neuroscience has revealed important differences in the cognitive processes underlying judgments of harm and purity violations. In particular, research has demonstrated that whether a violation was committed intentionally vs accidentally has a larger impact on moral judgments of harm violations (e.g. assault) than purity violations (e.g. incest). Here, we manipulate the instructions provided to participants for a moral judgment task to further probe the boundary conditions of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…ROIs were defined as all voxels within a 9-mm radius of the peak voxel that passed threshold in the contrast "false belief > false photo" (P < 0.001, uncorrected; k > 16, computed via 1000 iterations of a Monte-Carlo simulation, Slotnick et al 2003). We used the same ROI selection parameters as previous neuroimaging research examining ToM regions (Tsoi et al 2018;Dungan and Young 2019). See Supplementary Table 1 for peak coordinates and Supplementary Fig.…”
Section: Roi Analysesmentioning
confidence: 99%
“…ROIs were defined as all voxels within a 9-mm radius of the peak voxel that passed threshold in the contrast "false belief > false photo" (P < 0.001, uncorrected; k > 16, computed via 1000 iterations of a Monte-Carlo simulation, Slotnick et al 2003). We used the same ROI selection parameters as previous neuroimaging research examining ToM regions (Tsoi et al 2018;Dungan and Young 2019). See Supplementary Table 1 for peak coordinates and Supplementary Fig.…”
Section: Roi Analysesmentioning
confidence: 99%
“…If separate moral "foundations" do not exist (see also Schein & Gray, 2018), what are we to make of the many studies revealing correlations between interesting phenomena and measurements of fairness, loyalty, authority, and purity (Dungan & Young, 2019;Graham et al, 2009Graham et al, , 2016Graham & Haidt, 2010)? The answer is to pivot our understanding of "foundations" away from the modules of evolutionary psychology and back to the "themes of ethical discourse" of anthropology (Shweder et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Previous behavioral studies showed that people tend to make more strictly moral judgments in the non-purity domain and judge the purity domain to be more moral ( Landy and Goodwin, 2015 ; Olatunji et al, 2016 ). The imaging and electrophysiological studies also showed that the processing of purity-based moral judgment was different from that in other domains ( Dungan and Young, 2019 ; Jiang et al, 2020 ). So far, numerous empirical studies have formed two competing hypotheses ( Wagemans et al, 2018 ).…”
Section: Introductionmentioning
confidence: 93%